2020
DOI: 10.1101/2020.11.12.20230763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological responses to SARS-CoV-2 following non-hospitalised infection: clinical and ethnodemographic features associated with the magnitude of the antibody response

Abstract: ObjectiveTo determine clinical and ethnodemographic correlates of serological responses against the SARS-CoV-2 spike glycoprotein following mild-to-moderate COVID-19.DesignA retrospective cohort study of healthcare workers who had self-isolated due to COVID-19.SettingUniversity Hospitals Birmingham NHS Foundation Trust, UK (UHBFT).Participants956 health care workers were recruited by open invitation via UHBFT trust email and social media.InterventionParticipants volunteered a venous blood sample that was teste… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…Analysis of anti-IgG responses directed against the S1 domain in 2,112 persons with confirmed symptomatic SARS-CoV-2 infection at ~63 days after symptom onset revealed that people with overweight or obesity were less likely to be antibody-negative ( Petersen et al., 2020 ). These findings were corroborated by analysis of non-hospitalized individuals with symptoms of COVID-19 and relatively greater IgG responses against the spike protein in people with obesity ( Shields et al., 2020 ).…”
Section: Immune Responses In People With Obesity Diabetes and Sars-mentioning
confidence: 78%
“…Analysis of anti-IgG responses directed against the S1 domain in 2,112 persons with confirmed symptomatic SARS-CoV-2 infection at ~63 days after symptom onset revealed that people with overweight or obesity were less likely to be antibody-negative ( Petersen et al., 2020 ). These findings were corroborated by analysis of non-hospitalized individuals with symptoms of COVID-19 and relatively greater IgG responses against the spike protein in people with obesity ( Shields et al., 2020 ).…”
Section: Immune Responses In People With Obesity Diabetes and Sars-mentioning
confidence: 78%
“…The resulting curvilinear model (Figure 4) confirmed that the highest index S/C values can be expected in plasma from advanced age donors and donations collected soon after COVID-19 recovery. Obesity has been associated with increased COVID-19 severity [28][29][30] and with greater IgG response, 31 and while the current study did not evaluate donor body mass index in relation to SARS-CoV-2 antibody levels in plasma donations, these might be additional factors to be considered in CP collection.…”
Section: Effect Of Plasma Donor Demographics On Sars-cov-2 Antibodiesmentioning
confidence: 86%
“…Obesity has been associated with increased COVID‐19 severity 28–30 and with greater IgG response, 31 and while the current study did not evaluate donor body mass index in relation to SARS‐CoV‐2 antibody levels in plasma donations, these might be additional factors to be considered in CP collection.…”
Section: Effect Of Plasma Donor Demographics On Sars‐cov‐2 Antibodiesmentioning
confidence: 86%
“…It is not possible to draw robust conclusions on the associations of antibody response with age, sex, ethnicity or comorbidities, and although disease severity positively correlated with higher IgG antibody titres in a number of studies, distinguishing causation from correlation is not possible. More recent evidence shows that while responses may be of lower magnitude in milder cases, they are still elicited and may be protective-although evidence on response patterns in milder illness remains in short supply [164,169].…”
Section: Summary Of Findingsmentioning
confidence: 99%